PACING STRATEGIES IN MEN’S AND WOMEN’S WORLD RECORD MARATHON PERFORMANCES AND OLYMPIC GAMES AND WORLD CHAMPIONSHIP’S WINNING PERFORMANCES (Kinesiology, 2024)
The aims of this study were to compare marathon pacing profiles between major championships winning races and world record (WR) races in men’s and women’s long-distance runners. Percentages of mean race speeds (%RS) for each 5 km section and last 2,195 m were compared between the latest 12 men’s and 8 women’s marathon WRs and the most recent 14 men’s and 14 women’s performances leading to either World Championship or Olympic Games (championships) gold medals, and between sexes in championships, through analysis of variance. Additionally, the coefficient of variation in pace (%CV) was compared through independent samples t-tests. %RS during the first 5 km was greater in WRs than championships in men (p=.010, d = 1.07), with a subsequent even pacing profile. More negative pacing profiles were adopted in championships than WRs in men (p